1999
DOI: 10.1159/000054478
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Administered Murine Leptin Stimulates Plasma Arginine-Vasopressin Secretion and Increases the Level of mRNA Expression in the Supraoptic Nucleus of Conscious Rats

Abstract: The product of the ob gene protein, leptin, has been suggested to function as an endogenous mediator of the cardiovascular system via sympathetic nerve activity. Moreover, extensive distribution of leptin receptor-like immunoreactivity has been demonstrated in the choroid plexus, cerebral cortex, hippocampus, thalamus and hypothalamus, especially in the paraventricular nucleus (PVN) and supraoptic nucleus (SON). In this study, we have investigated the in vivo effects of leptin on plasma arginine-vasopressin (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…We recently reported that administration of leptin (10–400 pmol/rat i.c.v.) induces increases in plasma AVP levels and AVP gene expression in the PVN and SON in the same experimental model as done in this experiment [17]. AVP is a potent secretagogue for ACTH secretion and plays a role as a coregulator, with CRH, on pituitary corticotroph cells [18, 19].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We recently reported that administration of leptin (10–400 pmol/rat i.c.v.) induces increases in plasma AVP levels and AVP gene expression in the PVN and SON in the same experimental model as done in this experiment [17]. AVP is a potent secretagogue for ACTH secretion and plays a role as a coregulator, with CRH, on pituitary corticotroph cells [18, 19].…”
Section: Discussionmentioning
confidence: 92%
“…Colocalization of CRH and AVP is observed in parvocellular neurons of the PVN, and both peptides are secreted into the hypophysial-portal circulation by certain stimuli [16]. We recently reported that intracerebroventricular administration of leptin causes increases in plasma AVP levels and AVP mRNA expression in the PVN and supraoptic nucleus (SON) of conscious rats [17]. AVP secretion into the portal blood potentiates the effect of CRH on ACTH secretion from the anterior pituitary [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Our results add new evidence in favour of an inhibitory effect of leptin on HPA axis function in a different stress paradigm, the insulin-stimulated HPA axis activity. The mechanism by which leptin inhibited HPA axis response in this design could be due to direct effects at the hypothalamic [7, 8, 9]and adrenal [13]levels rather than upon the pituitary gland [28]; however, the main site of action of leptin appears to be the hypothalamus. In fact, such an inhibitory effect of leptin on low glucose-stimulated CRH output by perifused hypothalami has been reported [28].…”
Section: Discussionmentioning
confidence: 99%
“…The long variant of leptin receptor (Ob-Rb) has been found in the hypothalamus [5, 6]; leptin increases hypothalamic CRH- [7]and vasopressin (AVP)-ergic [8]functions, although an inhibitory effect of leptin on the CRH-ergic function in ob/ob mice has also been described [9]. Ob-Rbs have been found in normal and tumoral anterior pituitary cells of different mammals [10, 11]; activation of these receptors is likely to stimulate ACTH secretion [12].…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod alone did not influence Avpr1a mRNA expression either in the brain or in the testes. In rats intracerebroventricular administration of leptin significantly increased vasopressin mRNA expression in the supraoptic nucleus of the hypothalamus (Yamamoto et al, 1999). In another study central administration of leptin to rats, has been shown to activate Avpr1a in the paraventricular nucleus of the hypothalamus to regulate neuroendocrine axes such as the hypothalamus-pituitary-adrenal axis (Morimoto et al, 2000).…”
Section: Discussionmentioning
confidence: 92%